Achillea millefolium L. Extract Attenuates the Nephrotoxicity Induced by Acetaminophen in Rats: Achillea millefolium attenuates acetaminophen nephrotoxicity - Jamshidi, Hamid Reza; Lotfaliani, Mohamad Reza; Ghorbani, Shaghayegh; Hassanshahi, Jalal (Iranian Journal of Pharmaceutical Sciences, 2024)
Acetaminophen can put the kidneys at risk of serious damage by affecting the renal antioxidant system and its cellular pathways. Achillea millefolium L. has been found to have antioxidant properties. This study aimed to determine the effect of Achillea millefolium L. (Ach) extract on acetaminophen-induced nephrotoxicity in rats. In this experimental research, 36 male Wistar rats were used. High-performance liquid chromatography (HPLC) analyzed Ach compounds. Animals were randomly assigned to six groups (n=6), which included vehicle, Ach 300 mg/kg, acetaminophen, acetaminophen + Ach (50, 150, and 300 mg/kg). Then, animals received acetaminophen (Single dose, 500 mg/kg), and after 1 hour, they received solutions containing saline/Ach as a single dose by oral gavage. After 24 hours, blood urea nitrogen (BUN) and serum creatinine were determined using the relevant kit. Also, the malondialdehyde (MDA) concentration and the activity of glutathione peroxidase (GPx), catalase, and superoxide dismutase (SOD) were measured by the spectrophotometric method. Also, hematoxylin and eosin staining methods obtained renal tissue damage scores (RTDS). The results revealed that acetaminophen significantly increased the serum creatinine, BUN, RTDS, and MDA concentration and decreased the catalase, GPx, and SOD enzymes activity levels in renal tissues of the acetaminophen-administered rats versus the control (P<0.05). Ach treatment could significantly ameliorate these changes in acetaminophen + Ach (300 mg/kg) compared to the acetaminophen group (P<0.05). The present study revealed that Ach may protect against renal injury induced by acute acetaminophen poisoning, at least through its antioxidant effect.